Perbedaan Kecukupan Energi dan Status Gizi Siswa Membawa Bekal dan Tidak Membawa Bekal Ke Sekolah - Cindy Claudia Nurulita; Bambang Wirjatmadi (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2019)
Background: The school age is growth and development era towards adolescence, and if nutritional disorders occur during this period, it will have a major impact on the next life cycle. One of the direct causes the occurrence of nutritional problems is unbalanced meal intake. Since the intake of foods that contain nutrients balanced is essential for growth and development, especially in childhood. One of the messages of a balanced nutritional guidelines for elementary school children that is bringing meal.Objectives: to study the difference of adequacy energy level and nutritional status of students who packed meal from home and not packed meal to schoolMethods: this research was an observational analytical with case control design which was located in Pacarkeling 1 Elementary School Surabaya on March – April 2019. The sample was 34 students in grade 4 and 5, also to the number of each group of 17 students. Sampling method using simple random sampling. The research Variables are adequacy difference of energy, nutritional status, students who bring meal in school. Data was analyzed by independent sample t-test. Data was collected through interview using food recall 2x24 hours, anthropometry data using weight and high measurement. Results: This study showed that there was difference of adequacy energy (p=0.011) and nutritional status (p=0.014) of students who packed meal to school and those who do not bring packed meal to school Conclusions: There was a significance difference between energy needs level and nutritional status of students who packed meal to school and those who do not bring packed meal to school ABSTRAK Latar Belakang: Masa usia sekolah ialah masa tumbuh kembang anak menuju masa remaja sehingga rentan terkena gangguan gizi. Masa usia sekolah memiliki dampak yang cukup besar untuk masa kehidupan selanjutnya. Penyebab utama adanya gangguan gizi ialah konsumsi makanan yang tidak seimbang. Konsumsi makanan yang cukup mengandung zat gizi seimbang yang sangat penting untuk tumbuh kembang anak. Berdasarkan pedoman dari gizi seimbang untuk anak sekolah dasar yaitu membawa bekal makanan ke sekolahTujuan: mempelajari perbedaan kecukupan energi dan status gizi antara siswa membawa bekal dan tidak membawa bekal ke sekolahMetode: Metode penelitian bersifat observasional analitik dengan design case control yang berlokasi di SDN Pacar keling 1 Surabaya pada Maret-April 2019. Total sampel penelitian adalah sebanyak 34 sampel dengan jumlah setiap kelompok sebesar 17 sampel. Pengambilan sampel menggunakan simple random sampling, Variabel penelitian ini yaitu kecukupan energi, siswa membawa bekal dan tidak membawa bekal dan status gizi. Data dianalisis dengan uji independent T-test. pengukuran asupan makanan menggunakan metode wawancara menggunakan recall 2x24 jam dan instrument yang digunakan adalah meliputi timbangan berat badan digital, microtoise dan kuesionerHasil: terdapat perbedaan kecukupan energi (p= 0,014) dan status gizi (p= 0,011) siswa membawa bekal dan tidak membawa bekal.Kesimpulan: Kesimpulan penelitian ini adanya perbedaan yang signifikan pada tingkat kecukupan energi, dan status gizi siswa membawa bekal dan tidak membawa bekal. sebaiknya, anak sekolah terutama sekolah dasar memperhatikan pemilihan jenis makanan sesuai dengan kebutuhan zat gizi dalam sehari.